Multicultural counseling: The strategy of social fasilitator of post-conflict education and psychosocial guidance in multicultural society - Widaningtyas, Adoniati Meyria; Sutanti, Natri (Universitas Negeri Yogyakarta, 2022)
Unfortunately, multicultural problems manifested in patterns of thought, attitude, and behavior of intolerance are still seen in many societies over the past decade. It started to become common that certain groups attacked other ethnic and racial groups thereby causing conflict. This might be due to the handling of cases that are not ideal and appropriate, situations of intolerance, and social conflicts that have a wide impact, including causing psychological problems such as anxiety, hatred, violence, or depression. This study aimed to critically examine psychological coping strategies carried out in various countries to assist post-conflict victims with trauma, especially in multicultural societies. This study used an integrative review approach to analyze nine selected articles about psychological strategy and social education for post-conflict settings from 2010 to 2021 by reputable journals or publications. The results showed that the post-conflict victim handling strategy in various countries is carried out using psychosocial approaches and counseling/narrative therapy which are considered the most effective to help victims with trauma. Multicultural skills are an important part of post-conflict psychological handling, and hence is recommended multicultural counseling as a post-conflict psychological treatment and social education model is widely applied by societies with a high level of diversity.